Mepolizumab: an alternative therapy for idiopathic chronic eosinophilic pneumonia with glucocorticoid intolerance - Adam Kisling; Jason Jones; Caleb Hixson; David Hostler; Jordanna Hostler (BioExcel Publishing Ltd, 2020)
A 55-year-old woman with cough-variant asthma presented for 1 month of worsening wheezing, cough, and dyspnea refractory to treatment. Initial laboratory findings revealed profound peripheral eosinophilia, and a chest computed tomography showed bi-apical consolidation. Bronchio-alveolar lavage demonstrated alveolar eosinophilia. She was diagnosed with idiopathic chronic eosinophilic pneumonia (ICEP). Her peripheral eosinophilia and respiratory symptoms improved rapidly with high-dose systemic corticosteroid therapy. However, she was intolerant to corticosteroid monotherapy due to non-compliance and psychological adverse effects. Mepolizumab was initiated as a steroid-sparing agent, resulting in successful therapy for 2 years without relapse or adverse effects. Mepolizumab is an interleukin-5 (IL-5) antagonist monoclonal antibody, which is a targeted therapy for diseases mediated by eosinophil activity and eosinophil proliferation. Mepolizumab is typically used in ICEP refractory to steroids, but this case supports its use in cases of glucocorticoid intolerance. Further study of IL-5 antagonist therapies for ICEP may identify an alternative treatment modality for patients in whom the adverse effects of corticosteroids pose a challenge.